Carbon-siliceous nanocomposites via the method of sol-gel technology for selective coatings of solar collectors - Musiy, R.; Khairnasov, S.; Semenyuk, I. (Видавництво Львівської політехніки, 2012)
It was developed the selective coating by new type for the solar heat collectors. It has been used the carbon–siliceous nanocomposite obtained via sol–gel technology method. The comparative investigations of the obtained coating and the sample of SunSelect firm (Germany) were carried out. The distinctive peculiarity is the preparation of the coating by a high cost technology of the vacuum evaporation. The independent measurements have been done under the irradiation of the natural solar flow of radiation and the simulator of the solar spectrum.
Keywords: carbon – siliceous nanocomposites; sol–gel technology; selective coatings; solar heat collectors